Biomarkers for Early Complications of Endothelial Origin After Allogeneic Hematopoietic Stem Cell Transplantation: Do They Have a Potential Clinical Role? - Lia, Giuseppe; Giaccone, Luisa; Leone, Sarah; Bruno, Benedetto (Frontiers in Immunology, 2021)
Endothelial cell (EC) dysfunction causes a number of early and life-threatening post hematopoietic stem cell transplant (HCT) complications that result in a rapid clinical decline, include graft-vs.-host disease (GVHD), transfusion associated thrombotic microangiopathy (TA-TMA), and sinusoidal obstruction syndrome (SOS). Post-HCT endothelial dysfunction occurs as a result of chemotherapy, radiotherapy, infections, proinflammatory cytokines and allogeneic reactivity. Despite major advances in transplant immunology and improvements in supportive care medicine, these complications represent a major obstacle for successful HCT. In recent years, different biomarkers have been investigated for early detection of post-transplant endothelial cell dysfunction, but few have been validated. In this review we will define GVHD, TA-TMA and SOS, summarize the current data available in HCT biomarker research and identify promising biomarkers for detection and diagnosis of early HCT complications.